Західноєвропейський та візантійський типи цивілізації: ставлення до злочину й покарання - Крисюк, Ю.; Krysyuk, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено проблему ставлення до злочину та покарання крізь призму західноєвропейського й візантійського менталітетів. Доведено, що основна цивілізаційна відмінність між ними – унормованість суспільного та державного життя. Розглянуто аномію як один зі способів поведінки індивіда в суспільстві. Досліджено основні типи аномічної поведінки особистості, охарактеризовано кожну з них. Визначено психо- логічні й соціальні наслідки інституціональної кризи сучасного українського суспільства.The article highlights the issue related to crime and punishment through the prism of Western European and Byzantine mentality. It is proved that the basic civilizational difference between them – the ordering of public life. The main conclusion: «If the representatives of the Byzantine civilization seek freedom outside the scope of the rule of law, the freedom of the West is possible and acceptable only as a conscious voluntary compliance of the law every individual without exception». Anomie is considered as one of the modes of behavior of the individual in society. A term coined in the scientific revolution E. Durkheim, is a state of society where a significant part of the citizens, aware of the existence of moral and social norms and laws that apply to them indifferently or negatively. Analysis of the main types of anomichnogo individual behavior, characterized by each of them. Defined psychological and social consequences of the institutional crisis of modern Ukrainian society.
The Western European and Byzantine Type of Civilization: the Relation to Crime and Punishment
Keywords: злочин; покарання; аномія; менталітет; Західна Європа; Візантія; crime; punishment; anomie; mentality; Western Europe; Byzantium